Avaliação das características químicas e eletroquímicas do etanol obtido do mesocarpo do coco babaçu para uso em célula a combustível - CARDOSO, Ziel dos Santos (2017)
This work intends to avaluate the potential use of ethanol from coconut mesocarp babassu in fuel cells. Babassu ethanol was obtained through the hydrolysis and fermentation processes, respectively. Pt, PtRh and PtRu electrodes were prepared on carbon Vulcan XC-72R by reduction method and applied as electrocatalysts on the ethanol oxidation reaction. Samples of carbon steel 1020 were used in essay of oxidation metal surfaces in ethanol medium. The ethanol obtained from mesocarp of babassu coconut was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and High Performance Liquid Chromatography with Refractive Index Detector (HPLC-RID). X-Ray Spectroscopy by Energy Dispersion (EDS), Snanning Electron Microscopy (SEM), Stripping CO, Cyclic Voltammetry, Chonoamperometry, Differantial Electrochemical Mass Spectrometry on-line (DEMS) were used to characterize the synthesized eletrocatalysts. The carbon 1020 steel plates were immersed in ethanol medium and evaluated periodically using analytical balance, SEM and Optical Microscopy (OM). The results showed that babassu ethanol has the same profile as the commercial ethanol obtained from sugarcane. The PtRu/C electrocatalyst presented higher active area and higher catalytic activity compared to the other materials studied. The current efficiency for CO2 production was less than 1% for all studied electrocatalysts, showing that the oxidation of babassu ethanol produces less pollutants than commercial ethanol. The study of metallic surface corrosion showed that the corrosive action of babassu ethanol is similar to that of sugarcane ethanol, with approximate corrosion rates.